2019
DOI: 10.1002/jcp.28971
|View full text |Cite
|
Sign up to set email alerts
|

Mst1 deletion reduces septic cardiomyopathy via activating Parkin‐related mitophagy

Abstract: Cardiomyocyte function and viability are highly modulated by mammalian Ste20-like kinase 1 (Mst1)-Hippo pathway and mitochondria. Mitophagy, a kind of mitochondrial autophagy, is a protective program to attenuate mitochondrial damage.However, the relationship between Mst1 and mitophagy in septic cardiomyopathy has not been explored. In the present study, Mst1 knockout mice were used in a lipopolysaccharide (LPS)-induced septic cardiomyopathy model. Mitophagy activity was measured via immunofluorescence, Wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…In response to LPS-mediated mitochondrial damage, deletion of mammalian Ste20-like kinase 1 (Mst1) activates mitophagy to protect mitochondria. However, repressing Parkin-mediated mitophagy abolishes the positive influence of Mst1 deletion on mitochondrial protection and myocardial cell viability (Shang et al, 2020). Dexmedetomidine (DEX) alleviates LPSinduced apoptosis and the inflammatory response of macrophages via PINK1-mediated mitophagy (Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In response to LPS-mediated mitochondrial damage, deletion of mammalian Ste20-like kinase 1 (Mst1) activates mitophagy to protect mitochondria. However, repressing Parkin-mediated mitophagy abolishes the positive influence of Mst1 deletion on mitochondrial protection and myocardial cell viability (Shang et al, 2020). Dexmedetomidine (DEX) alleviates LPSinduced apoptosis and the inflammatory response of macrophages via PINK1-mediated mitophagy (Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…While canonical PINK-Parkin-dependent mitophagy preserves mitochondrial and cardiac function in diabetic mice with high-fat diet-induced cardiomyopathy [173], defects in PINK-Parkin-dependent mitophagy leads to severe cardiac complications in animal models of Duchenne muscular dystrophy [172]. The expression of negative regulators of cardiomyocyte mitophagy, such as the mammalian Ste20-like kinase 1 (Mst1), has also been documented in an experimental model of septic cardiomyopathy [174]. Notably, Mst1 depletion attenuates lipopolysaccharide (LPS)-induced cardiomyocyte death and preserves cardiac function via promoting Parkin-dependent mitophagy [174].…”
Section: Mitochondrial Quality Control In Cardiovascular Diseasementioning
confidence: 99%
“…The expression of negative regulators of cardiomyocyte mitophagy, such as the mammalian Ste20-like kinase 1 (Mst1), has also been documented in an experimental model of septic cardiomyopathy [174]. Notably, Mst1 depletion attenuates lipopolysaccharide (LPS)-induced cardiomyocyte death and preserves cardiac function via promoting Parkin-dependent mitophagy [174]. Moreover, a role for the adenine nucleotide translocator (ANT) complex in mitophagy regulation via interaction with TIM23 has been described [175].…”
Section: Mitochondrial Quality Control In Cardiovascular Diseasementioning
confidence: 99%
“…In addition, mitophagy in cardiomyocytes is regulated by mammalian Ste20-like kinase 1 (Mst1), which rapidly increases in cardiomyocytes upon LPS treatment or diabetic stress. Mst1 depletion attenuates LPSinduced cardiomyocyte death or diabetic cardiomyopathy and improves cardiac function via promoting Parkin-dependent mitophagy (Shang et al, 2019). Further evidence reveals that the inhibition of mitophagy by Mst1 is associated with SIRT3, whereas depletion of SIRT3 restores cardiac function when Mst1 is overexpressed in diabetic cardiomyopathy .…”
Section: Mitophagy In Cardiovascular Disease (Cvd) Pink1/parkin-depenmentioning
confidence: 93%
“…Evidence suggests that decreased PINK1/Parkindependent mitophagy is associated with development of dystrophic cardiomyopathy (Kang et al, 2018). Recently, it has been reported that PINK1/Parkin-dependent mitophagy is regulated by several factors (Sun et al, 2014;Tahrir et al, 2017;Yu et al, 2017;Li G. et al, 2018;Pickles et al, 2018;Thai et al, 2018;Xiong et al, 2018;Ren J. et al, 2019;Shang et al, 2019). PTEN FIGURE 3 | Overview of mitochondrial biogenesis, fission and fusion in cardiomyocytes.…”
Section: Mitophagy In Cardiovascular Disease (Cvd) Pink1/parkin-depenmentioning
confidence: 99%